2018
DOI: 10.1007/s00436-018-6049-6
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid-modified silver nanoparticles as a novel therapeutic agent against Acanthamoeba

Abstract: Free-living amoebae belonging to Acanthamoeba genus are widely distributed protozoans which are able to cause infection in humans and other animals such as keratitis and encephalitis. Acanthamoeba keratitis is a vision-threatening corneal infection with currently no available fully effective treatment. Moreover, the available therapeutic options are insufficient and are very toxic to the eye. Therefore, there is an urgent need for the development of more effective anti-amoebic agents. Nanotechnology approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…has been already confirmed [15,16,17]. It has been demonstrated in previous studies in our laboratory that silver and gold nanoparticles were well absorbed and showed activity against Acanthamoeba strains belonging to the T4 genotype [18]. Other authors have also confirmed that nanoparticles may enhance the anti-amoebic effect of biguanides, for example, chlorhexidine digluconate and other compounds [19,20,21].…”
Section: Introductionsupporting
confidence: 59%
“…has been already confirmed [15,16,17]. It has been demonstrated in previous studies in our laboratory that silver and gold nanoparticles were well absorbed and showed activity against Acanthamoeba strains belonging to the T4 genotype [18]. Other authors have also confirmed that nanoparticles may enhance the anti-amoebic effect of biguanides, for example, chlorhexidine digluconate and other compounds [19,20,21].…”
Section: Introductionsupporting
confidence: 59%
“…Recently, natural products coated nanoparticles have shown potent antiacanthamoebic effects. Tannic acid, Oleic acid, Cinnamic acid, Hesperidin, Naringin, Periglaucine A, and Betulinic acid coated nanoparticles have shown the step forward in the development of nanomedicine against challenging infections caused by Acanthamoeba (Padzik et al 2018;Anwar et al 2018bAnwar et al , 2019aMahboob et al 2018). Moreover, various plant extracts coated nanoparticles have also shown promise in the drug discovery against Acanthamoeba infections.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed on the Jatropha curcas, Jatropha gossypifolia and Euphorbia milii extracts combined with nanoparticles exhibited that such combination caused signi cant reduction of the Acanthamoeba trophozoites with low cytotoxic effect to human cells [23]. In our previous studies we con rmed that tannic acid-modi ed silver nanoparticles showed increased anti-amoebic activity and less cytotoxicity to human cells in comparison to the pure silver nanoparticles [22]. In this study we revealed that tannic acid-modi ed silver nanoparticles conjugated with contact lens solutions exhibited even better anti-amoebic activity in relation to the cytotoxicity than in results obtained in our previous studies where we tested pure silver nanoparticles conjugates [45].…”
Section: Discussionmentioning
confidence: 83%
“…Brie y, the cytotoxicity assays were performed using a broblast HS-5 (ATCC CRL-11882) cell line as described in our previous studies [22]. A commercial kit for the evaluation of drug-induced cytotoxic effects based on the measurement of lactate dehydrogenase (LDH) activity released to the media (Pierce LDH cytotoxicity assay kit 88953, 88954) was used as per protocol.…”
Section: Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation